Asuhan Kebidanan Komprehensif pada Ny. R Umur 26 Tahun G2P1A0 Dengan Preeklamsia di Wilayah Kerja Puskesmas Bantarkawung Kabupaten Brebes Tahun 2023 - Rina Amelliana; Himatul Khoeroh; Mupliha Mupliha (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
According to the World Health Organization (WHO), in 2021 around 329,000 women died due to complications related to pregnancy or childbirth throughout the world, MMR in Indonesia until 2022 was 305/100,000 live births, WHO data for 2021 states the Infant Mortality Rate (IMR) in the world amounted to 235 deaths per 100,000 live births. Brebes Health Office (2022) MMR 50 cases, IMR 259 cases. Data from Bantarkawung Community Health Center (2022) MMR 1 case, IMR 5 cases. This researcher is able to carry out comprehensive midwifery care for Mrs. R aged 26 years with Preeclampsia using Varney's seven-step obstetric management and SOAP. Based on the background above, the problem formulation is how Comprehensive Midwifery Care for Mrs. R aged 26 years in the working area of the Bantarkawung Community Health Center, Brebes Regency in 2023. The research design used by the author is qualitative descriptive research. Comprehensive Care for Mrs.R found problems early in pregnancy with preeclampsia. Labor was induced, and the newborn was normal. During the postpartum period, the uterine involution process goes well. Conclusion: Through this scientific paper, it is hoped that health center health workers can maintain and improve the quality of health services in accordance with service standards and the application of theory.